Super- and sub-Lorentzian effects in the Ar-broadened line wings of HCl gas - Tran, Ha; Ebert, Volker; Hartmann, Jean-Michel (The journal of chemical physics, 2017)
Using previously recorded spectra of HCl diluted in Ar gas at room temperature for several pressure conditions, we show that the absorptions in between successive P and R transitions are significantly different from those predicted using purely Lorentzian line shapes. Direct theoretical predictions of the spectra are also made using requantized classical molecular dynamics simulations and an input HCl-Ar interaction potential. They provide the time evolution of the dipole auto-correlation function (DAF) whose Fourier-Laplace transform yields the absorption spectrum. These calculations very well reproduce the observed super-Lorentzian behavior in the troughs between the intense lines in the central part of the band and the tendency of absorption to become sub-Lorentzian in the band wings between high J lines. The analysis shows that the former behavior is essentially due to incomplete collisions which govern the DAF at very short times. In addition, the increasing influence of line-mixing when going away from the band center explains the tendency of absorption to become more and more sub-Lorentzian in the wings.
Gesehen am 23.08.2018